Portuguese version of the Posttraumatic Stress Disorder Checklist for DSM‐5 (PCL‐5): Comparison of latent models and other psychometric analyses. Issue 7 (23rd January 2020) - Carvalho, Teresa; da Motta, Carolina; Pinto‐Gouveia, José
Abstract: Objective: This psychometric study explores the Portuguese version of the Posttraumatic Stress Disorder (PTSD) Checklist (PCL‐5). It aims to clarify the best‐fitting latent structure among competing PTSD models ( Diagnostic and Statistical Manual of Mental Disorders‐fifth edition [ DSM‐5 ], Dysphoria, Dysphoric Arousal, Anhedonia, Externalizing Behavior, And Hybrid models) and its implications for PTSD measurement. Method: Psychometric analyses were conducted in a sample from the general population of firefighters ( N  = 446), except the temporal stability, which was tested in a subsample of 100 participants. Results: The models presented significant differences in a global fit. The Hybrid model presented the best‐fitting structure, but the DSM‐5 model showed more favorable reliability and convergent validity in Confirmatory Factor Analyses. The DSM‐5 model also proved to be internally consistency, temporally stable, and presented convergent validity. Conclusion: The Portuguese version of PCL‐5 is reliable and valid. The findings suggest the appropriateness of the DSM‐5 model to assess PTSD symptomatology, encouraging its use in clinical, and research settings.